The Stability of Metasedimentary Rock in Ranau, Sabah, Malaysia - Ismail Abd Rahim; Baba Musta (Indonesian Journal on Geoscience, 2018)
DOI: 10.17014/ijog.5.1.23-31The aim of this paper is to determine the stability of slopes and to propose preliminary rock cut slope protection and stabilization measures for Paleocene to Middle Eocene Trusmadi Formation along Marakau-Kigiok in Ranau, Sabah, Malaysia. The rock of Trusmadi Formation is slightly metamorphosed and dominated by interbeds of sandstone with quartz vein (metagreywacke), metamudstone, shale, slate, sheared sandstone, and mudstone. The rock unit can be divided into four geotechnical units namely arenaceous unit, argillaceous unit, interbedded unit, and sheared unit. Twelve slopes were selected for this study. Geological mapping, discontinuity survey, kinematic analysis, and prescriptive measure were used in this study. Results of this study conclude that the potential modes of failures are planar and wedge. Terrace, surface drainage, weep holes, horizontal drain, vegetation cover, wire mesh, slope reprofiling, and retaining structure were proposed protection and stabilization measures for the slopes in the studied area.